Pengaruh Penambahan Plant Growth Promoting Bacteria (Azospirillum sp.) Pada Kultivasi Chlorella sp. Dalam Penyisihan COD Di Limbah Cair Tahu - Mesy Susri Darsi; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Chlorella sp. can be used as a solution to tofu liquid waste problems. Therefore, it is important to develop this microalgae cultivation technique. One of them is by using the Azospirillum sp. which can support growth and can increase the efficiency of removal from tofu liquid waste. In this research, the measurement of the growth rate of the microalgae Chlorella sp. and COD removal. The research conducted in batches with the addition of bacteria at 5 different levels, namely 0 (without the addition of Azospirillum sp.), the addition of Azospirillum sp. as many as 0.25; 0.50; 0.75; and 1 (% v / v). Processing is carried out for 13 days by irradiating sunlight in a photobioreactor. Based on the research results, the highest growth rate of Chlorella sp. and the best COD removal efficiency of 0.17/ day and 86.84% were obtained from the addition of Azospirillum sp. 1% v/v on the thirteenth day. Keywords: Azospirillum sp., Chlorella sp., COD, Contact Time, Tofu Liquid Waste